DAMPAK PELAKSANAAN PILKADA DI KABUPATEN NIAS SELATAN DI MASA PANDEMI COVID-19: TINJAUAN YURIDIS UNDANGUNDANG NOMOR 2 TAHUN 2020 TENTANG KEBIJAKAN KEUANGAN NEGARA DAN STABILITAS SISTEM KEUANGAN UNTUK PENANGANAN PANDEMI COVID-19 - Titah Ndruru; Vera Wheni Setijawati Soemarwi (Fakultas Hukum Universitas Tarumanagara, 2021)
Simultaneous Pilkada in the midst of a pandemic raises legal problems in relation to aspects of health and democracy. The problem is the extent to which the Government considers the choice between protecting public health in the South Nias Regency area with the replacement of the Pilkada in the South Nias Regency area and how the impact of the Pilkada in South Nias Regency during the Covid-19 pandemic will be. The research method used is a normative juridical research method. The results of the study indicate that in the implementation of the 2020 Pilkada in the midst of the Covid-19 pandemic in South Nias Regency, the Government always considers aspects of health protection for the community by always adhering to health protocols. Pilkada should not ignore public health and security, which are far more important than democratic parties in the context of changing regional head elections. The impact of the Pilkada in South Nias Regency during the Covid-19 pandemic includes the mandate of regulations that are in effect still being implemented, the constitutional rights of Pilkada participants and the community are still fulfilled, reducing the practice of local government leadership which is led by too many temporary officials, preventing budget swelling, while The negative is the risk of COVID-19 transmission is higher, the potential for fraudulent practices is increasingly vulnerable, the refusal of the Regional Head Election has the potential to increase the number of abstentions.